Usefulness of enhancement-perfusion mismatch in differentiation of CNS lymphomas from other enhancing malignant tumors of the brain - Goyal, Pradeep; Kumar, Yogesh; Gupta, Nishant; Malhotra, Ajay; Gupta, Saurabh; Gupta, Sonali; Mangla, Manisha; Mangla, Rajiv (Quantitative Imaging in Medicine and Surgery, 2017)
Background: Surgical planning and treatment options for primary or secondary central nervous system lymphomas (PCNSL or SCNSL) are different from other enhancing malignant lesions such as glioblastoma multiforme (GBM), anaplastic gliomas and metastases; so, it is critical to distinguish them preoperatively. We hypothesized that enhancement-perfusion (E-P) mismatch on dynamic susceptibility weighted magnetic resonance (DSC-MR) perfusion imaging which corresponds to low mean relative cerebral blood volume (mean rCBV) in an enhancing portion of the tumor should allow differentiation of CNS lymphomas from other enhancing malignant lesions. Methods: We retrospectively reviewed pre-treatment MRI exams, including DSC-MR perfusion images of 15 lymphoma patients. As a control group, pre-treatment DSC-MR perfusion images of biopsy proven 18 GBMs (group II), 13 metastases (group III), and 10 anaplastic enhancing gliomas (group IV) patients were also reviewed. Region of interests (ROIs) were placed around the most enhancing part of tumor on contrast-enhanced T1WI axial images and images were transferred onto co-registered DSC perfusion maps to obtain CBV in all 4 groups. The mean and maximum relative CBV values were obtained. Statistical analysis was performed on SPSS software and significance of the results between the groups was done with Mann-Whitney test, whereas optimal thresholds for tumor differentiation were done by receiver operating characteristic (ROC) analysis. Results: The enhancing component of CNS lymphomas were found to have significantly lower mean rCBV compared to enhancing component of GBM (1.2 versus 4.3; P